Breaking ice for Arctic oil : the epic voyage of the SS Manhattan through the Northwest Passage - Coen, Ross Allen (University of Alaska Press, 2012)
In 1969, an icebreaking tanker, the SS Manhattan, was commissioned by Humble Oil to transit the Northwest Passage in order to test the logistical and economic feasibility of an all-marine transportation system for Alaska North Slope crude oil. Proposed as an alternative to the Trans-Alaska Pipeline, the Manhattan made two voyages to the North American Arctic and collected volumes of scientific data on ice conditions and the behavior of ships in ice. Although the Manhattan successfully navigated the Northwest Passage-closing a five-hundred-year chapter of Arctic exploration by becoming.